A deskriptive profile of isometric muscle strength and muscle strength imbalance in young tennis players - Zuša, A.; Lanka, J.; Èupriks, L.; Dravniece, I. (Baltic Journal of Sport and Health Sciences, 2015)
Background. Tennis is assumed as asymmetric sport, prolonged training practice could affect muscle strength imbalance. Muscle strength functional ratio imbalance could be a reason for poor posture, physical weakness and increased risk of injury. The purpose of the research was to evaluate young tennis players` main muscle group strength topography and to investigate the level of different muscles groups` bi-lateral and contra-lateral imbalance. Methods. The participants of the study were six young right handed competitive tennis players (girls, age 11.4 ± 0.5 years, tennis experience 4.7 ± 0.6 years). Examination of main muscles groups was performed with an isokinetic dynamometer. Results. Young tennis players have pronounced bi-lateral imbalance between shoulder joint extensors and flexors (25%), internal and external rotators (36%), left elbow flexors and extensors (58%), wrist pronator and supinator (the right hand 17%, left 48%), hip flexors and extensors (35%); knee joint flexors and extensors (60%); ankle dorsal flexors and plantar flexors (59%); spine and abdominal muscles (48%). It was detected that young tennis players have pronounced contra-lateral imbalance between right and left internal rotators of the shoulder joint (27%) and external rotators (26%), wrist joint supinators (41%). Conclusions. To avoid the increase in muscle bi-lateral imbalance it is highly recommended to pay more attention to shoulder adductors and shoulder external rotators, elbow flexors and extensors, wrist supinators and extensors, knee extensors, ankle plantar flexors and spine flexors. For contra-lateral imbalance prevention in addition to train non-dominant upper extremity muscles: shoulder internal and external rotators, wrist supinators.